Navigating Sustainable Supply Chains in Pakistan's Textile Industry: Addressing Regulatory, Infrastructural, and Social Challenges for Enhanced Sustainability - Malik, Tariq Ali (My University, 2024)
Abstract: This research investigates the key challenges and opportunities associated with implementing sustainable supply chain practices within the textile sector of Pakistan, focusing on two prominent companies: Interloop and Kohinoor Textile Mills (KTML). The study aims to address the regulatory, infrastructural, and social challenges that impact the effectiveness and sustainability of supply chains in this sector. The research employs a qualitative approach, utilizing semi-structured interviews with industry professionals who have a minimum of five years of experience in supply chain management. These interviews are designed to explore the nuances of regulatory compliance, infrastructural constraints, and social dynamics within the textile industry. The study captures in-depth insights from participants in various roles, including procurement specialists, senior managers, compliance officers, and operations managers, providing a comprehensive understanding of the sector’s challenges and opportunities. The findings reveal that the regulatory landscape in Pakistan's textile industry is marked by outdated compliance systems and high tariffs, which, while intended to protect domestic industries, often result in inefficiencies and increased costs. The research identifies specific regulatory gaps and calls for updated policies that better align with international standards and support sustainable practices. In terms of infrastructure, the study highlights significant barriers, such as inadequate facilities, technological limitations, and energy crises, which impede the implementation of sustainable practices. The analysis shows that while training programs are in place to address these issues, their effectiveness is compromised by systemic challenges and a lack of skilled labour. Recommendations include investing in infrastructure improvements, enhancing training programs, and developing more robust support systems for sustainability initiatives. Social challenges are also critical, with the study uncovering issues related to supplier engagement and workforce management. The low morale and educational gaps among workers pose difficulties for effective management and the implementation of sustainable practices. The research suggests that improving social conditions, enhancing educational programs, and fostering better relationships with suppliers are essential for overcoming these challenges.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management